MESH NETWORK DEVELOPMENT PROJECT IN GREAT STONE INDUSTRY PARK - Pei Ping; Yu. N. Petrenko (Системный анализ и прикладная информатика, 2016)
Wireless Mesh network (WMN) are increasingly becoming popular as low cost alternatives to wired network for providing broadband access to users. A wireless mesh network (WMN) is a communication networks made up of radio nodes organized in a mesh topology. It is also a form of wireless network. Wireless mesh networks often consist of mesh clients, mesh routers and gateways. The mesh clients are often laptops, cell phones and other wireless devices while the mesh routers forward traffic to and from the gateways, which may, but need not, be connected, to the Internet. In this paper, we discuss different radio frequency range in wireless connected to Access Point (AP) and the project from Belarus – China great stone industry park in Mesh network. The China-Belarus industrial park is a territorial entity with the area of approximately 80 sq. km with a special legal status for the provision of comfortable conditions for business conducting. The Park is located in a unique natural complex 25 km far from Minsk, the capital of the Republic of Belarus. It is in close proximity to the international airport, railway lines, a transnational highway Berlin-Moscow. The result of analysis shows distribution of AP and covering services in great stone industry park. Mesh network provides robustness and load balancing in wireless networks communication.